La fauna bentónica y su relación con la contaminación orgánica en el Río Negro, Prov. Chaco (Argentina) Estudio Preliminar - Varela, María E.; Di Persia, Danilo H.; Bonetto, Argentino A. (Ecosur, 2023)
The Negro River (Chaco Province), an affluent of the Paraná River, receives the effluents coming from the several industries established along its margíns. As a result, its lower strech is variably affected by processes of organic polution, determining a strong change in the limnological conditions, particulary conceming to the dissolved oxygen, which becomes almost exhausted in areas of considerable extention. In consequence, the general conditions for the animal life are severe, and only those species with special adaptations can survive. This paper develops the general study of the benthic fauna, with special reference to the differente species of oligochaetes and their populations, in relation to the processes of polution. Several aspects referred to the valué of oligochaetes as biological indicators of the water quality are also discussed.